An Investigation of the Impact of Financial Literacy on Households’ Financial Well-Being: An Emerging Market Study - Chetioui, Hajar; Bouchikhi, Yassine El; Makhtari, Mohamed; Sahli, Meriem; Lebdaoui, Hind (International Journal of Economics and Financial Issues, 2024)
In view of the amplified inflation rates and economic stagnation in a number of countries in recent times, financial vulnerability became a key concern in both developed and developing economies. The current study advocates financial literacy is a key to lessen financial vulnerability and promote financial well-being. We propose and test a thorough model investigating the key mechanisms contributing to financial literacy, and how it contributes to individuals’ financial well-being in the context of an emerging market (i.e., Morocco). The mediating effects of indebtedness and financial behavior are also scrutinized. Based on survey data collected from a sample of 848 respondents from Morocco, the conceptual model was assessed using structural equation modeling. Our findings suggest financial literacy as a key to lessen financial vulnerability and promote financial well-being. Policy makers in Morocco and developing countries, where financial vulnerability is more prevalent, may use the current study findings to promote effective education programs to improve citizens’ financial literacy and well-being. Our findings also convey no impact of education on financial literacy, suggesting that education programs in Morocco are still not yet aware of the importance of financial literacy as a key shaping students’ career and financial well-being. Education policy makers are therefore urged to incorporate financial education and literacy as a key component in all education programs. Financial education programs should also take into consideration demographic disparities and therefore design financial education programs based on the target group to better delineate financial literacy in education programs.